On Supercritical Sobolev Type Inequalities and Related Elliptic Equations - Ubilla-Lopez, P (Springer New York LLC, 2016)
Sobolev type embeddings for radial functions into variable exponent Lebesgue spaces are studied. In particular, the following inequality is proved: let B⊂ RN, N≥ 3 , be the unit ball, and let H0,rad1(B) denote the first order Sobolev space of radial functions, and 2 ∗= 2 N/ (N- 2) the corresponding critical Sobolev embeddding exponent. Let r= |x| , and p(r) = 2 ∗+ rα, with α> 0 ; then (Formula presented.). We point out that the growth of p(r) is strictly larger than 2 ∗, except in the origin. Furthermore, we show that for p(r) = 2 ∗+ rα, with 0<α<min{N2;N-2}, the supremum in (0.1) is attained. Finally, we prove that associated elliptic equations admit nontrivial radial solutions. This is somewhat surprising since the nonlinearities have strictly supercritical growth except in the origin. © 2016, Springer-Verlag Berlin Heidelberg.